Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1084/jem.20200817
|View full text |Cite
|
Sign up to set email alerts
|

Group 2 innate lymphoid cells support hematopoietic recovery under stress conditions

Abstract: The cell-cycle status of hematopoietic stem and progenitor cells (HSPCs) becomes activated following chemotherapy-induced stress, promoting bone marrow (BM) regeneration; however, the underlying molecular mechanism remains elusive. Here we show that BM-resident group 2 innate lymphoid cells (ILC2s) support the recovery of HSPCs from 5-fluorouracil (5-FU)–induced stress by secreting granulocyte-macrophage colony-stimulating factor (GM-CSF). Mechanistically, IL-33 released from chemo-sensitive B cell progenitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…43 However, it is possible that non-myeloid mature blood cells such as innate lymphoid type 2 cells (ILC2) may also contribute to regulation of the hematopoietic compartment in a STAT1-dependent manner and further studies are necessary to define the contributions of these cells. 49 We found that stimulating NOD1, but not NOD2, promotes hematopoiesis in the absence of the microbiota in a STAT1-dependent manner. These data clarify previous reports that identified multiple innate immune pathways, including NOD1 and STAT1, as separately promoting hematopoiesis in a microbiota-dependent manner.…”
Section: Discussionmentioning
confidence: 71%
“…43 However, it is possible that non-myeloid mature blood cells such as innate lymphoid type 2 cells (ILC2) may also contribute to regulation of the hematopoietic compartment in a STAT1-dependent manner and further studies are necessary to define the contributions of these cells. 49 We found that stimulating NOD1, but not NOD2, promotes hematopoiesis in the absence of the microbiota in a STAT1-dependent manner. These data clarify previous reports that identified multiple innate immune pathways, including NOD1 and STAT1, as separately promoting hematopoiesis in a microbiota-dependent manner.…”
Section: Discussionmentioning
confidence: 71%
“…ILC2 production of type 2 cytokines that results in AAMs recruitment (19,57) may be considered detrimental in controlling Mtb. This may be contradictory as Sudo et al (58) reported that ILC2s produce GM-CSF, a cytokine known to activate macrophages and control Mtb infection (59). This may explain the slight increase in the ILC2 and IL-13 levels in the LBTI group.…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that ILC2s create local tissue microenvironments that are enriched for GM-CSF and provide context-dependent support for particular myeloid compartments, such as eosinophils or DCs. Indeed, bone marrow ILC2s were recently reported to increase GM-CSF expression and to support hematopoietic recovery under conditions of stress hematopoiesis following treatment with 5fluorouracil (Sudo et al, 2021). Further studies are thus required to reveal the more subtle consequences of lung hematopoietic Csf2-deficiency with the necessary spatial resolution.…”
Section: Discussionmentioning
confidence: 99%